Public Perceptions towards Mayor's Decisions Making and Its Government Performance of Surakarta City, Central Java, Indonesia - Suwardi, Doktor; Sugiyarti , Sri Risis (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to study the relation of decision concept to the Mayor of Surakarta’s Performance, Central Java, Indonesia. Research analysis was conducted by comparing two data as independent variable: mayor’s attitude to government apparatus and mayor’s attitude to the public. The dependent variable was perceived performance. Data were obtained through conducting face-to-face interview with 550 respondents. The size of sample fulfilled the criterion of 5% margin error at significance level of 95. The result of research shows that public appreciates highly the mayor performance. Positively perceived performance of mayor is endorsed by the mayor’s attitude in facing some problems. The mayor tends to have different attitude in facing problems. He tends to be firmer to governmental apparatus but to deal with the people with problems more wisely.